The Outer Membrane Lipoprotein Tp0136 Stimulates Human Platelet Activation and Aggregation Through PAR1 to Enhance Gq/Gi Signaling - Xu, Qiu-Yan; Wang, Yong-Jing; Lin, Li-Rong; Liu, Li-Li; Yang, Tian-Ci (Frontiers in Immunology, 2022)
Background: Chancre self-healing, a typical clinical phenomenon of primary syphilis, is essentially wound healing. The first response to a wound is constriction of the injured blood vessels and activation of platelets to form a fibrin clot. However, the role of Treponema pallidum in platelet activation and clot formation remains unclear. Objectives: We aimed to elucidate the role of the outer membrane Treponema pallidum lipoprotein Tp0136 in human platelet activation and aggregation and explore the related mechanism. Methods: A series of in vitro experiments were performed to assess the effects of Tp0136 on human platelet activation and aggregation. The effect of Tp0136 on platelet receptors was studied by detecting PAR1 protein levels and studying related receptor sites. The involvement of the Gq/Gi signaling pathway downstream of PAR1 was explored. Results: Tp0136 significantly accelerated the formation of human platelet clots as well as platelet adhesion to and diffusion on fibrinogen to promote platelet aggregation. Tp0136 also potentiated P-selectin expression and PF4 release to promote platelet activation and downregulated PAR1 expression. The activation and aggregation induced by Tp0136 were reverted by the specific PAR1 antagonist RWJ56110 and the human PAR1 antibody. In addition, Tp0136 significantly enhanced Gq and Gi signaling activation, thereby triggering p38 phosphorylation and Akt-PI3K activation, increasing the release of intraplatelet Ca2+ and attenuating the release of cytosolic cAMP. Furthermore, the specific PAR1 antagonist RWJ56110 significantly suppressed Gq and Gi signaling activation. Conclusions: Our results showed that the Treponema pallidum Tp0136 protein stimulated human platelet activation and aggregation by downregulating PAR1 and triggered PAR1-dependent Gq and Gi pathway activation. These findings may contribute to our understanding of chancre self-healing in the early stages of syphilis.